Meningkatkan Aktivitas dan Hasil Belajar IPA Siswa Kelas V untuk Menanamkan Karakter Peduli Lingkungan Menggunakan Integrasi Model Pembelajaran Problem Based Learning, Talking Stick dan Media Audio Visual di Sekolah Dasar - Sutan Arief Wandhani; Muhsinah Annisa (CV. ITTC INDONESIA, 2023)
This research was aimed at describing teacher activities, analyzing student activities, learning outcomes and describing the environmentally caring character of science content in fifth grade elementary school students using the integration of Problem Based Learning, Talking Stick and audio visual media learning models. Data collection in this research was carried out using the test method which was obtained through individual written tests to measure student learning outcomes and non-test methods obtained through observation of teacher activities and student activities. This type of research is Classroom Action Research (PTK) which is carried out in 2 cycles, where cycle I consists of 2 meetings and cycle II consists of 1 meeting. The subjects of this research were 17 grade V elementary school students in the even semester of the 2022/2023 academic year. The results of this research show that the percentage of student activity initially reached 39% with the criterion